Bloodstream Infection Etiology among Children and Adults - Svetlana I. Kolesnichenko; Alyona V. Lavrinenko; Lyudmila L. Akhmaltdinova (International Journal of Microbiology)
Every year in the world, sepsis occurs in 31.5 million people, and the number of deaths reaches 5.3 million per year. There are not enough studies that describe etiological structure of sepsis pathogens in different groups of population of the Republic of Kazakhstan. In this study, we have investigated difference of local sepsis etiology and antibiotic susceptibility among children and adults. A total 200 blood samples were examined using the standard and express method of identification of bloodstream pathogens. The determination of antimicrobial sensitivity was carried out by the disc-diffusion method according to CLSI guidelines. Overall, 23/90 (25.5%) positive blood cultures were isolated from adult patients and 43/110 (39%) from pediatric patients. It was found that children are statistically more often affected with bacterial bloodstream infection than adults (p<0.05). The Gram-positive bacteria are the leading cause of sepsis in both groups: S. epidermidis (35.5%) in pediatric patients and S. aureus (21.7%) in adults. However, statistical significance was detected in pediatric patients (p<0.05). The number of resistant strains of S. epidermidis (MRSE) in the group of children was 66.7%, while in adults, all S. epidermidis was resistant to azithromycin and cefoxitin (MRSE). S. aureus strains from adult patients and children had a similar picture of antibiotic patterns. The proportion of MRSA in pediatric patients was 16, 6%, and in adult patients, 20%. Enterobacterales (39%) were the second cause of sepsis in adult patients. 62.5% of Enterobacterales strains isolated from adults were phenotypically identified as ESBL, while in pediatric patients, 25% of ESBL producers were isolated. We have noted the resistance to antibiotics that are prescribed according to protocols of treatment of the Republic of Kazakhstan in the strains isolated from the patient’s blood.